Szorstkość lnu i zapach wełny. Wykonywanie ściegu za ściegiem jako forma dialogu z naturą - Kępa, Ewa (Strategie komunikacyjne i procesy twórcze, 2022)
Making traditional handicraft is a process of creative construction and deconstruction of the meanings from the past in current socio-cultural contexts. It is also a form of exploring the world, the way of human participation in the 'world-in-formation'. In the presented article I treat hand-made textiles as a dialogical process of creating knowledge, creating reality and communicating with the past. I am focus on the work of the hands of those who process organic materials in the bosom of nature. I weave autoethnographic threads into the presented text. Threads which are experiences accompanying me in the process of recreating the stitches of an old linen tablecloth made at the beginning of the 20th century.